1984
DOI: 10.1182/blood.v63.6.1353.1353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thalassemia and microcytosis on the hematologic and vasoocclusive severity of sickle cell anemia

Abstract: The characteristic clinical heterogeneity of sickle cell anemia (HbSS) may be, in part, a result of its interactions with alpha-thalassemia. Although alpha-thalassemia clearly affects some hematologic features of HbSS, its role in modulating the vasoocclusive severity of disease is not clear. To further explore this relationship, we examined the incidence of painful episodes, acute chest syndrome, aseptic bone necrosis, and leg ulcers in 3 patient groups with sickle cell disease: (1) 2,147 patients over age 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(41 citation statements)
references
References 43 publications
1
38
0
2
Order By: Relevance
“…α Thalassemia was associated with a reduction of MCV; (Figure S4). Increased HbA 2 in sickle cell anemia‐α thalassemia is a result α/δ‐globin dimerizing more readily than α/β S ‐globin . α Thalassemia modified the relationship between HbA 2 and MCV: without α thalassemia, a regression of HbA 2 on MCV yielded a slope of −0.028; with α thalassemia, the slope was −0.038 (a −33% change, P = 0.0339) (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…α Thalassemia was associated with a reduction of MCV; (Figure S4). Increased HbA 2 in sickle cell anemia‐α thalassemia is a result α/δ‐globin dimerizing more readily than α/β S ‐globin . α Thalassemia modified the relationship between HbA 2 and MCV: without α thalassemia, a regression of HbA 2 on MCV yielded a slope of −0.028; with α thalassemia, the slope was −0.038 (a −33% change, P = 0.0339) (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…HbA 2 was measured by DEAE Cellulose column chromatography (CSSCD) or high performance liquid chromatography (Walk‐PHaSST, PUSH, β‐thalassemia cohort). HbF was measured by alkali denaturation (CSSCD) and HPLC (Walk‐PHaSST, PUSH, β‐thalassemia cohort).…”
Section: Methodsmentioning
confidence: 99%
“…Alguns autores descrevem interação de hemoglobinas variantes com talassemia alfa. Na anemia falciforme é descrita interação benéfica com talassemia alfa, ocorrendo diminuição da anemia hemolítica, inibição da polimerização intracelular da hemoglobina S e diminuição da intensidade de hemólise (18,19) .…”
Section: Discussionunclassified
“…In addition, frequent painful episodes and chronic pain significantly decrease the quality of life (QOL) in patients with SCD. Historically, it has been shown that advancing age, high hemoglobin, low fetal hemoglobin (HbF) 60 and coinheritance of a-thalassemia 61 are associated with increased number of VOCs in children and adults with SCD. Among the experimental biomarkers, elevated plasma thrombospondin 1, a secretory product of activated platelets that promotes sickle vascular adhesion, plasma levels 33,62 and imbalance of apelin (vasodilator) and endothelin 1 (vasoconstrictor) 63 are associated with a vasoocclusive phenotype.…”
Section: Vaso-occlusive Pain Crisismentioning
confidence: 99%
“…119,120 Coinheritance of a-thalassemia has mixed effects on disease severity, as it decreases hemolysis 121,122 and risk of stroke 60,123 but increases the frequency of VOCs and avascular necrosis of bone. 61 Nongenetic factors such as environmental factors (eg, high wind speed, humidity, cold temperatures, and air pollution), infection, asthma, smoking, socioeconomic status, and access to care can adversely affect the disease course. 117,124,125 Unfortunately, there is no systematic way of accurately predicting which patient will have worse disease and die early preemptively by taking into account the factors listed above.…”
Section: Disease Severity and Mortalitymentioning
confidence: 99%